STRUCTURE AND MECHANISM OF WRITING IN FOREIGN LANGUAGE TEACHING - Ataboyev, Isroil; Rustamov Ilkhom Tursunovich (Журнал иностранных языков и лингвистики, 2023)
We assume that the device - and in particular its phased design - creates problem maps and these can only be represented in relational form. The morphological perspective tries to highlight the thematic structures of different buildings and their dynamics.